Lime-based adsorbent for use in exhaust gas treatment equipment and method for producing said lime-based adsorbent
A lime-based adsorbent with hydrogel-forming additives addresses the CDS technology's moisture content limitations, ensuring improved flowability and reduced clogging, thereby enhancing the efficiency and stability of the CDS process.
Patent Information
- Application Number
- JP2022517859
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-23
- Filing Date
- 2020-09-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-09-22
AI Technical Summary
Circulating dry scrubber (CDS) technology faces limitations in increasing moisture content without causing sticky behavior and clogging in ducts and reactors, leading to operational instability and shutdowns, despite its effectiveness in contaminant removal.
A lime-based adsorbent comprising at least 70% Ca(OH)2 and 0.2% to 10% hydrogel-forming additives like superabsorbent polymers or cellulose ethers, which allow for higher moisture content without adverse effects, maintaining flowability and preventing clogging.
The lime-based adsorbent enhances moisture retention and flowability, improving the CDS process efficiency by allowing higher moisture content, reducing clogging, and extending the adsorbent's operational cycles.
Smart Images

Figure 0007603669000002 
Figure 0007603669000003 
Figure 0007603669000001
Abstract
Description
[Technical field]
[0001] In a first aspect, the invention relates to an adsorbent suitable for use in an exhaust gas treatment plant. In a second aspect, the invention relates to a premix for use in a process for producing said adsorbent. In a third aspect, the invention relates to a process for producing an adsorbent suitable for use in an exhaust gas treatment plant. In a fourth aspect, the invention relates to the use of said adsorbent in an exhaust gas treatment process. In a fifth aspect, the invention relates to an exhaust gas treatment process using said adsorbent. [Background technology]
[0002] Flue gas contains substances that are considered harmful to the environment, and flue gas treatment is increasingly being carried out to remove and neutralize these harmful substances and pollutants. Various processes are used for flue gas treatment, including scrubbing technology. The first type of such technology is the wet scrubber technology, which uses wet scrubber units and generally works by contacting the target compounds or particulate matter with a scrubbing liquid (water for dust, a solution or suspension of reagents to target specific compounds). The second type of scrubbing technology is the dry scrubbing system and the semi-dry scrubbing system (also called semi-wet scrubbing system). Compared to wet scrubber units, these systems do not saturate the treated flue gas with moisture. They may not add moisture or may only add an amount of moisture that can evaporate without condensing in the flue gas. The main applications of dry or semi-dry scrubbing equipment are mainly related to the capture and removal of acid gases, such as sulfur oxides and hydrochloric acid, from combustion sources. In this disclosure, the term "circulating dry" in the expressions "circulating dry scrubber device" or "circulating dry scrubber installation" or "circulating dry scrubber systems" or "circulating dry scrubber unit or circulating dry scrubber facility" refers to either a "circulating dry scrubber" or a "circulating semi-dry scrubber".
[0003] Circulating dry scrubber (CDS) technology was first developed for SO2 removal in coal-fired power plants. It is now also used to treat flue gas from industrial furnaces and boilers fueled by biomass, industrial waste, or municipal solid waste. CDS technology typically implements a CDS process and includes a CDS unit, which can be integrated into a larger global CDS installation. The CDS process is based on the recirculation of the residue recovered from particulate control equipment, which consists of unreacted sorbent, reaction products, and optionally fly ash.
[0004] CDS units typically include a reactor that receives the exhaust gas and a sorbent, typically a calcium-based sorbent. The reactor is accompanied by a particulate control device that filters solids (also called residue, which includes unreacted sorbent, reaction products, and optionally fly ash) from the exhaust gas. These solids are then partially recycled to the reactor through a recycle loop. Fresh sorbent can be added before or after the reactor, periodically or continuously. In most cases, water is injected into the reactor or over the solids for temperature control, improved pollutant removal performance, and reactivation of the residue. Some CDS facilities have a CDS unit and may have a hydrator (also called a slaking unit). In these facilities, quicklime CaO, which is hydrated before entering the CDS unit, is used in the CDS process. Some other CDS facilities do not have a hydrator and the fresh sorbent injected is hydrated lime.
[0005] In the first method of handling the CDS process, the residue is moistened before reinjection into the reactor. In the second method of handling the CDS process, water is injected directly into the reactor.
[0006] Unfortunately, even though CDS technology is effective in removing pollutants, there is a limit to the amount of water that can be added, and water addition remains a key factor in removing these pollutants. In fact, it is known that acid gases can be captured at a higher efficiency by increasing the moisture content in the exhaust gas, but it should be noted that if the moisture content is lower than the dew point, corrosion problems may occur, especially in the reactor.
[0007] If the residue is moistened before reinjection into the reactor, the maximum moisture content relative to the mass of the dry recycle residue observed on a commercial scale is 10% by weight, more frequently 2-7% by weight. If the moisture content exceeds 10%, sticky behavior and clogging phenomena occur on the duct walls in both the recycle loop and the reactor, leading to unstable operation up to the complete shutdown of the flue gas scrubbing system.
[0008] When water is directly injected into the reactor, clogging occurs in the reactor even though the recycled material does not carry the water, which adversely affects the exhaust gas treatment.
[0009] There is a need to provide an adsorbent and an exhaust gas treatment process that allows the operation of a CDS process with an increased moisture content without adversely affecting the cyclic dry scrubbing process. In particular, it is desirable to at least reduce the sticky behavior and clogging phenomena of the recycled material in the duct walls, the recycle loop, and the reactor.
[0010] The applicant's document WO2018185328 discloses an adsorbent for use in a circulating dry scrubber, comprising at least 50 wt.% Ca(OH)2 and 0.5 wt.% to 8 wt.% silicon or aluminum or a combination thereof, the amounts of which are expressed in their elemental form and based on the total weight of the adsorbent in a dry state. The adsorbent further comprises 1 to 12 wt.% bound water based on the total weight of the adsorbent in a dry state, and 1 to 40 mol.% of calcium is not in the form of Ca(OH)2, CaCO3 or CaO. Such an adsorbent is obtained by a process comprising the following steps: - Providing quicklime and water to the hydrator; - slaking said quicklime with water in a hydrator via non-wet route; - Recovery of lime-based sorbent at the outlet of the hydrator; Here, the process is characterized by further including a step of adding at least the following first additive: - silicon-containing compounds, preferably selected from the group consisting of silicates, sodium silicates, metasilicates, sodium metasilicates, kieselguhr, diatomite, diatomaceous earth, precipitated silica, rice husk ash, silica fume, perlite, silicic acid, amorphous silica, calcium silicate or combinations thereof, and / or - an aluminium-containing compound, preferably selected from the group consisting of aluminate, sodium aluminate, aluminium trihydroxide, boehmite, calcium aluminate or combinations thereof, and / or - a compound containing silicon and aluminum, the compound being selected from the group consisting of aluminosilicates, sodium aluminosilicates, fly ash, blast furnace slag, vermiculite paper ash, or combinations thereof. Wherein, before or during the slaking step, the molar ratio between silicon or aluminum or a combination thereof and calcium fed to the hydrator is less than or equal to 0.2 and greater than or equal to 0.02.
[0011] Although such sorbents show good performance in terms of pollutant capture and mobility in CDS facilities, there is a need for other sorbent compositions with improved performance derived from different sources. Summary of the Invention
[0012] According to a first aspect, the present invention relates to a lime-based sorbent suitable for use in flue gas treatment processes comprising: - at least 70% by weight of Ca(OH)2, preferably at least 80% by weight of Ca(OH)2, more preferably at least 90% by weight of Ca(OH)2, more preferably at least 95% by weight of Ca(OH)2, relative to the total weight of said lime-based adsorbent in dry form after drying at 150°C to constant weight, and - a first additive, which is at least 0.2% by weight and at most 10% by weight, preferably at least 1% by weight and at most 5% by weight, more preferably at least 1.2% by weight and at most 2.5% by weight, relative to the total weight of said lime-based adsorbent in dry form after drying to constant weight at 150°C, wherein this first additive is selected from among materials of natural or synthetic origin, in particular from the group of superabsorbent polymers (SAP) or from the group of cellulose ethers or a combination thereof.
[0013] The Ca(OH)2 present in the adsorbent can be qualitatively and quantitatively determined by conventional techniques known to those skilled in the art: the amount of calcium is measured by XRF, the crystal structure of the compound is analyzed by XRD, the proportion of calcium carbonate and / or calcium oxide, if present, and calcium hydroxide is determined by thermogravimetry on a sample dried to constant weight at 150°C.
[0014] The additives present in the adsorbent can be qualitatively and quantitatively determined by NMR by preparing samples dried to constant weight at 150° C. and then mixed in a deuterated solvent or mixture of deuterated solvents, preferably a mixture of DO and CD3CN, and then probe HR-MAS (high resolution magic angle spinning) for analysis in the semi-liquid state. 1 H NMR or 13 C NMR or a combination of both, and the solid samples were dried to constant weight at 150 °C. 1 Quantitative measurements by NMR can be made by comparing with a calibration curve obtained by preparing samples of the adsorbent containing various concentrations of the additive.
[0015] The term "hydrogel-forming material" according to the present invention includes both dehydrated hydrogels (i.e., in powder form) or hydrogels with trapped water, and also includes within its scope any intermediate forms, such as hydrogel-forming materials that contain 5% water or 10% water, yet are in powder form while still trapping ambient humidity.
[0016] Preferably, the first additive is selected from the following: - the group of hydrogel-forming materials of synthetic origin, including polyacrylates, polyacrylic acids, crosslinked products of polyacrylates and polyacrylic acids, or crosslinked products of acrylamide and acrylic acid copolymers, in particular those partially neutralized with sodium and / or potassium; or - a group of naturally occurring hydrogel-forming materials, including guar gum, alginate, dextran or xanthan gum, or combinations thereof; and / or - The group of cellulose ethers, including hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethylcellulose or hydroxyethylmethylcellulose (HEMC).
[0017] Preferably, the superabsorbent polymer is one or more selected from the group consisting of crosslinked polymers of acrylic acid or methacrylic acid, crosslinked graft copolymers of polysaccharide / acrylic acid or methacrylic acid, crosslinked terpolymers of acrylic acid or methacrylic acid / acrylamide / sulfonated acrylamide, and superabsorbent polymers of synthetic origin selected from the group consisting of alkaline earth or alkali metal salts thereof.
[0018] Preferably, the monomers selected for the preparation of the superabsorbent polymer are selected from acrylamide, acrylic acid, ATBS (acrylamidotertiarybutylsulfonate), NVP (N-vinylpyrrolidone), acryloylmorpholine, and / or itaconic acid, each of which is partially or fully basified.
[0019] Preferably, the superabsorbent polymer is a homopolymer or crosslinked copolymer in which acrylic acid is partially or completely basified. The superabsorbent polymer may be obtained by hydrophilic monomers such as diallyldialkylammonium, diallylaminoalkyl(meth)acrylate, dialkylaminoalkyl(meth)acrylamide, and cationic polymers containing quaternary ammonium salts thereof or acids thereof. More particularly, dimethylaminoethyl acrylate (ADAME), dimethylaminoethyl methacrylate (MADAME), acrylamidopropyltrimethylammonium chloride (APTAC) and / or methacrylamidopropyltrimethylammonium chloride (MAPTAC).
[0020] The synthetic superabsorbent polymers are generally crosslinked with a crosslinking agent selected from among N,N-methylenebisacrylamide (MBA), ethylene glycol dimethacrylate, 1,1,1-trimethylolpropane triacrylate, tetraallyloxyethane, tetraallylammonium chloride, divinylbenzene, metal salts or any crosslinking agent known to one skilled in the art.
[0021] Superabsorbent polymers are well known commercially available polymers.
[0022] According to the present invention, the hydrogel-forming material has a water adsorption capacity, expressed as the weight of deionized water relative to the weight of polymer, of less than 400 g / g, preferably 350 g / g or less, more preferably 300 g / g or less, in particular 250 g / g or less, and more particularly 200 g / g or less.
[0023] More specifically, according to the present invention, the hydrogel-forming material has a water adsorption capacity, expressed as the weight of deionized water relative to the weight of polymer, of 80 g / g or more, preferably 100 g / g or more.
[0024] Advantageously, the hydrogel-forming material has a water adsorption capacity, expressed as weight of deionized water per weight of polymer, of between 100 g / g and 200 g / g, more preferably between 120 g / g and 180 g / g, for example about 150 g / g.
[0025] The first additive in the present invention selected from among the hydrogel-forming materials can capture water at relatively low temperatures such as room temperature for its conditioning, but can also release water in the form of steam in the presence of Ca(OH)2 in a CDS unit or a dry scrubber injection (DSI unit) at operating temperatures comprised between 50°C and 350°C, preferably between about 150°C and 180°C. Moreover, the lime-based adsorbent combining the hydrogel-forming material and Ca(OH)2 preferably remains in the form of a powder to be injected during flue gas treatment.
[0026] The lime-based adsorbent according to the present invention can be sustained for multiple pass cycles through the CDS equipment in flue gas treatment, during which it alternates between a water capture step (eg, in a conditioning drum) and a water release step (in a CDS unit).
[0027] In one embodiment, the lime-based sorbent according to the invention further comprises sodium, wherein the amount of sodium, expressed as its equivalent NaO oxide form in said lime-based sorbent, measured by XRF, is at least 0.1% by weight, preferably at least 0.3% by weight, preferably at least 0.5% by weight, preferably at least 0.7% by weight, preferably at most 15% by weight, preferably at most 7% by weight, preferably at most 5% by weight, preferably at most 2.5% by weight relative to the total weight of said sorbent in dry form.
[0028] Preferably, the lime-based adsorbent according to the invention has a viscosity of at least 3 m 2 / g, preferably at least 10m 2 / g, more preferably at least 20m 2 / g, preferably at least 40m 2 / g, where the BET specific surface area is measured manometrically with nitrogen adsorption after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multipoint BET method described in the ISO 9277 / 2010E standard. In one embodiment of the present invention, the adsorbent has a specific surface area of 3 to 20 m 2 / g.
[0029] Advantageously, the lime-based adsorbent according to the invention has a pH of at least 0.01 cm 3 / g , preferably at least 0.05 cm 3 / g , more preferably at least 0.1 cm 3 / g , more preferably at least 0.15 cm 3 / g , more preferably at least 0.2 cm 3 / gIn one embodiment of the present invention, the adsorbent has a total BJH pore volume of 0.01 to 0.15, wherein the total BJH pore volume is measured by manometry with nitrogen adsorption after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multi-point BJH method described in the ISO 9277 / 2010E standard. cm 3 / g The BJH pore volume is comprised between
[0030] The particle size of lime-based sorbents, hydrated lime and additives can be measured in two ways depending on the nature of the sample. The first method is sieve analysis, where the dried sample is passed through a series of sieves with decreasing mesh sizes and the retained fraction on each mesh is weighted. The mesh sizes at which the powder retention is poorer than 2% of the powder weight are weighted as the first value d. max The mesh size that has a powder retention rate of more than 90% by weight of the powder is defined as the second value d min This method is limited by the mesh size of the sieve, so d larger than 30 μm is not possible. min It is used for samples with a particle size of 100 μm or less. In addition, it is possible to provide a depression in the sieve to force the sample to pass through.
[0031] A second method for measuring the particle size distribution of lime-based adsorbents, hydrated lime and additives is laser particle size measurement after ultrasonic treatment in a solvent, e.g. methanol, where the sample does not dissolve or gel. The first value is d max is defined as d 98 and the second value corresponds to d min is defined as d 10 The notation dx refers to the size distribution of a sample of particles, meaning that x% of the particles have a size less than or equal to a certain value, expressed in μm.
[0032] Preferably, the lime-based adsorbent in the present invention has a d of 1 mm or less, preferably 400 μm or less, more preferably 200 μm or less, more preferably 100 μm or less, preferably 80 μm or less, more preferably 40 μm or less, more preferably 30 μm or less. max d min is preferably 1 μm or more, preferably 2 μm or more, more preferably 5 μm or more, more preferably 10 μm or more, more preferably 20 μm or more, more preferably 30 μm or more.
[0033] In a preferred embodiment of the lime-based sorbent according to the invention, said Ca(OH)2, said first additive, is in the form of a powder blend comprising: - Value d max and d min Powder particles of slaked lime having a particle size distribution comprised in a first range; and - d overlapping or equal to said first range max and d min The powder particles of the first additive have a particle size distribution comprised within a second range of values.
[0034] It is very important that the particle size distribution of the powder particles of hydrated lime and the powder particles of the additive are close to each other in order to prevent segregation of the particles of hydrated lime and the particles of the additive.
[0035] According to a second aspect, the present invention relates to a premix for use in a process for the manufacture of a lime-based sorbent, said premix comprising: - at least 70% by weight, more preferably at least % by weight, of quicklime, based on the total weight of said premix in the dry state after drying to constant weight at 150°C; and - at least 0.2% by weight and up to 10% by weight, preferably at least 1% by weight and up to 5% by weight, more preferably at least 1.2% by weight and up to 2.5% by weight of a first additive, relative to the total weight of said premix in dry form after drying to constant weight at 150°C. This first additive here is selected from hydrogel-forming materials of natural or synthetic origin, in particular from the group of superabsorbent polymers (SAP), or from the group of cellulose ethers, or a combination thereof.
[0036] Providing such a premix could potentially be more advantageous in terms of logistics and costs for flue gas treatment plants that own hydrators.
[0037] Preferably, in the premix according to the invention, the powdered quicklime and the powdered first additive are in the form of a powder blend comprising: - the third range value d max and d min Powder particles of quicklime having a particle size distribution consisting of: - d overlapping or equal to the third range max and d min The powder particles of the first additive have a particle size distribution comprised within a fourth range of values.
[0038] It is important that the particle size distributions of the quicklime particles and the first additive particles are close to each other to prevent segregation of the particles in the premix.
[0039] According to a third aspect, the present invention relates to a method for producing a lime-based sorbent suitable for use in an exhaust gas treatment process, the method comprising the steps of: - Slaking quicklime with water in a hydrator via non-wet route; - recovering hydrated lime at the outlet of said hydrator; wherein the method further comprises adding at least a first additive; the first additive is selected from the group of hydrogel-forming materials of natural or synthetic origin, in particular from the group of superabsorbent polymers (SAPs) or from the group of cellulose ethers or from a combination thereof; The first additive is added before, during or after the slaking step and has a weight ratio to the weight of the slaked lime of 0.2-10 wt.%, preferably at most 5 wt.%, more preferably at most 2.5 wt.%, wherein the amount of slaked lime is expressed as equivalent CaO and the amount of the first additive is expressed as dry equivalent after drying at 150° C. to constant weight.
[0040] Preferably, in the manufacturing method according to the present invention, the first additive is selected from the following: - a group of hydrogel-forming materials of synthetic origin, including polyacrylates, polyacrylic acids, crosslinked products of polyacrylates and polyacrylic acids or crosslinked products of acrylamide and acrylic acid copolymers, especially those partially neutralized with sodium and / or potassium; - a group of naturally occurring hydrogel-forming materials including guar gum, alginate, dextran or xanthan gum or combinations thereof; or - The group of cellulose ethers, including hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethylcellulose or hydroxyethylmethylcellulose (HEMC).
[0041] The term "hydrator" in the sense of the present invention means a conventional single or multi-stage hydrator or mixer.
[0042] According to the invention, the term "slaking via the non-wetting route" refers to the following slaking of quicklime:
[0043] In the manufacturing method according to the invention, the slaking step is a "non-wet route" slaking mode, which designates a slaking mode via a dry route, via a semi-dry route or via a semi-dry route. In the non-wet route, the amount of water relative to the amount of quicklime is comprised between 0.6 and 1.2. The expression "non-wet route" excludes the slaking mode via a wet route and the slaking mode via a putty route. Each of these slaking routes is defined later in this specification.
[0044] In the dry hydration of quicklime, i.e., the "dry" slaking mode, the mass ratio of water to quicklime used in the dry slaking of quicklime is comprised between 0.6 and 0.7.
[0045] In the semi-dry hydration of quicklime, since it is a different slaking mode, hydration can be achieved with a larger excess of water, and the mass ratio of water to quicklime used in the semi-dry hydration of quicklime is composed of 0.85 to 1.2.
[0046] In the semi-dry hydration of quicklime, the mass ratio of water to quicklime used for slaking quicklime is 0.7 to 0.85.
[0047] In the "wet" slaking mode, the amount of water added is much larger than that strictly necessary for the slaking reaction, and the mass ratio of water to lime used in the slaking of quicklime is usually greater than 1.5. In this way, milk of lime, i.e. an aqueous suspension of hydrated lime particles, is obtained.
[0048] In the "putty route" slaking mode, the amount of water used in the slaking reaction is slightly less than that used in the "wet route" slaking, the mass ratio of water to quicklime used in the slaking of quicklime is usually more than 1.2 and less than 1.5, and the resulting product is in the form of a putty (lime putty).
[0049] In the manufacturing method according to the invention, the first additive is provided at least partially in solution or suspension and is added to the water and / or to the slaked lime and / or the first additive is provided at least partially in solid form and is added to the quicklime and / or to the slaked lime.
[0050] Preferably, the manufacturing method according to the present invention comprises the step of mixing powdered slaked lime and the first additive in powder form.
[0051] In one embodiment of the method for producing a lime-based adsorbent according to the present invention, the method comprises the following steps: - Slaking quicklime with water in a hydrator via non-wet route; - recovering hydrated lime at the outlet of said hydrator; - optionally drying the slaked lime; - optionally grinding the hydrated lime; - optionally, the slaked lime is air-classified and / or sieved to obtain a slaked lime; max and d min obtaining slaked lime having a particle size distribution in a first particle size range defined by: - d overlapping or included within said first range of particle sizes max and d min providing said first additive having a particle size distribution in a second range of particle sizes defined by: max and d min Mixing the first additive with the hydrated lime having a particle size distribution comprised of a first range of particle sizes defined by:
[0052] Preferably, the first additive has a d of 400 μm or less. max , and d of at least 1 μm minand the powdered slaked lime has been air classified or sieved to have a particle size distribution comprised within the range of 1 μm to 200 μm, or 1 to 20 μm, or 5 to 20 μm, or 20 to 35 μm, or 20 to 50 μm, or 50 to 100 μm, or 50 to 150 μm, or 100 to 200 μm.
[0053] In one embodiment of the present invention, the manufacturing method includes a preliminary step of size cutting of the hydrated lime particles and separation of the additive particles to remove fractions of particles below and above a predetermined value to provide hydrated lime particles and additive particles with similar size distributions to prevent segregation of the hydrated lime particles and additive particles. The size cutting step can be performed by passing the hydrated lime and / or additive particles through a series of sieves of a predetermined mesh size or by passing the hydrated lime and / or additive particles through an air classifier.
[0054] In one embodiment, the additive and / or hydrated lime are ground prior to the step of granule cutting or vice versa.
[0055] In another embodiment of the manufacturing method according to the present invention, the process comprises the following steps. -d max and d min providing quicklime having a predetermined particle size distribution in a third particle size range defined by: - d overlapping or included within said third range of particle sizes max and d min and providing the first additive having a particle size distribution in a fourth range of particle sizes defined by: max and d min and mixing said quicklime having a particle size distribution consisting of a third range of particle sizes defined by: - non-wet slaking the premix in a hydrator to obtain hydrated lime containing the first additive; - recovering hydrated lime at the outlet of said hydrator; - optionally drying the slaked lime; - optionally grinding the hydrated lime; Optionally, sieving or air classifying the hydrated lime.
[0056] In one embodiment of the process according to the invention, the process further comprises the step of adding a second additive, which is an alkali metal salt or hydroxide, before and / or during and / or after the slaking step, in an amount sufficient to obtain the slaked lime, the alkali metal content, expressed in terms of alkali metal oxide, being 0.2% by weight or more and 3.5% by weight or less, based on the total weight of the slaked lime.
[0057] Preferably, the alkali metal presalt or hydroxide is soluble in water, such as sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium phosphate, sodium persulfate or sodium acetate. Preferably, the alkali compound has a solubility in water of 50% or less at 20° C. g / dm 3 More than 100, preferably g / dm 3 More than 200, preferably g / dm 3 More than 300, preferably g / dm 3 More than 500, more preferably g / dm 3 That's all.
[0058] In one embodiment of the process according to the invention, the alkali metal salt or hydroxide is provided as a solid or in solution and is added to the water and / or the quicklime and / or the slaked lime. The alkali metal salt or hydroxide may be added in the process before and / or during and / or after the slaking step.
[0059] In one embodiment of the method according to the invention, the steps of drying the lime-based adsorbent and / or cutting the lime-based adsorbent into granules and / or grinding or pulverizing the lime-based adsorbent are carried out.
[0060] Advantageously, in the process according to the invention, the residence time during which the quicklime is slaked inside the hydrator is comprised between 5 and 45 minutes, preferably between 20 and 40 minutes and more preferably between 25 and 35 minutes.
[0061] In another embodiment of the process according to the invention, the quicklime is subjected to a size cutting to have particles comprised between a third numerical range and the first additive is subjected to a size cutting to have particles comprised between a fourth numerical range, the third numerical range and the fourth numerical range having an overlap, and the step of blending the quicklime and the first additive is included prior to the step of slaking.
[0062] According to a fourth aspect, the present invention relates to the use of a lime-based sorbent as disclosed herein and / or obtained from a manufacturing process as shown herein, in an exhaust gas treatment process.
[0063] According to a fifth aspect, the present invention relates to an exhaust gas treatment process in which a gas containing pollutants is circulated through a duct before reaching a particulate control device, characterized in that it includes a step of injecting the lime-based adsorbent presented in this specification.
[0064] The exhaust gas treatment can be a circulating dry scrubber process or a dry solvent injection (DSI) process.
[0065] The use of the adsorbent according to the invention in a circulating dry scrubber process provides a residue capable of carrying more water than prior art residues while maintaining good flowability of such residue in the CDS process, thereby allowing sticking in pipes, ducts or other parts of the circulating dry scrubber unit or equipment to be prevented.
[0066] The adsorbent according to the present invention provides a resid in a CDS process that exhibits good flowability characteristics even when the resid circulating in a circulating dry scrubber unit or facility has a high wetness, such as 10 wt. % or more.
[0067] It is believed that when the moisture content of the adsorbent-supported water is increased, the performance of the exhaust gas treatment device is significantly improved for the following reasons. - The addition of water may help with gas conditioning, particularly to reduce the reaction temperature and increase the relative humidity; - The added water is believed to make the remaining Ca(OH)2 available again for reaction; - The added water is believed to create favorable conditions locally around the solids in the reactor to enhance the activity of the sorbent, reaction products, and even fly ash (the added water is believed to promote the carbonated Ca, which is essential for acid gas removal (SO x The HCl and HF removal properties of the HCl-containing fluorine ...
[0068] If a smaller amount of recycled material can be used to feed the same amount of water to the reactor, the conditioning mixer and all associated equipment, especially the conveying devices (screws, air slides, etc.), can be made smaller, reducing not only the investment costs but also the utility and maintenance costs of running a CDS process.
[0069] During flue gas treatment using circulating dry scrubber units or installations, the sorbent particles enter into contact with the flue gas and form a suspension of reacted and unreacted sorbent particles and eventually other by-products. This suspension is filtered by a particulate control device. The pollutant-free flue gas is led to the stack, and the residue formed by reacted and unreacted sorbent particles and other by-products is reused for another cycle in the CDS unit. This residue can be recirculated in several portions. Fresh sorbent can also be introduced into the CDS unit at any time. Water is added to reactivate the reacted sorbent.
[0070] It is foreseen that water is added to the residue circulating in a circulating dry scrubber (CDS) unit or installation so that the adsorbent according to the invention has a water content of at least 5% by weight, preferably at least 7% by weight, preferably at least 10% by weight, preferably at least 12% by weight, preferably at least 15% by weight, relative to the dry mass of the residue.
[0071] As a function of the ratio of sulfur oxides and hydrochloric acid in the exhaust gases treated in the circulating dry scrubber unit or installation, the amount of water added onto the residue circulating in the circulating dry scrubber unit or installation can be adapted.
[0072] When the ratio of sulfur oxides to HCl is greater than 20, the amount of HCl is generally small and it is possible to add water to the residue circulating through the circulating dry scrubber unit or installation so that the moisture content relative to the dry mass is up to 20% by weight without risk of clogging the residue in the circulating dry scrubber unit or installation.
[0073] When the ratio of sulfur dioxide to HCl is less than 20, the amount of HCl is generally considered to be high and there may be more problems with clogging of the residue in the circulating dry scrubber unit or installation. Thus, when the ratio of sulfur dioxide to HCl is less than 20, the water on the residue circulating in the circulating dry scrubber unit or installation may be such that the water content on the dry mass of the residue is at least 2% by weight only.
[0074] In an embodiment, the flue gas treatment process according to the invention comprises the step of introducing an adsorbent according to the invention, or an adsorbent obtained from a manufacturing process as disclosed herein, into said circulating dry scrubber unit or installation.
[0075] One advantage of using the lime-based sorbent according to the invention in a dry sorbent injection process is that the additive can capture moisture, thereby minimizing adhesion to the sorbent storage silo or injection pipes connected to the flow gas duct.
[0076] Other characteristics and advantages of the invention will emerge from the non-limiting following description and by reference to the drawings and examples. [Brief description of the drawings]
[0077]
Figure 1
[0078]
Figure 2
[0079] According to the present invention there is provided a lime-based sorbent suitable for use in an exhaust gas treatment process, the lime-based sorbent comprising: - at least 70% by weight of Ca(OH)2, preferably at least 80% by weight of Ca(OH)2, more preferably at least 90% by weight of Ca(OH)2, more preferably at least 95% by weight of Ca(OH)2, relative to the total weight of said lime-based adsorbent in dry form after drying at 150°C to constant weight, and - a first additive which is at least 0.2% by weight and up to 10% by weight, preferably at least 1% by weight and up to 5% by weight, more preferably at least 1.2% by weight and up to 2.5% by weight, relative to the total weight of said lime-based adsorbent in dry form after drying at 150°C to constant weight. Here, the first additive is selected from hydrogel-forming materials of natural or synthetic origin, in particular from the group of superabsorbent polymers (SAPs), or from the group of cellulose ethers, or combinations thereof.
[0080] The Ca(OH)2 present in the adsorbent can be qualitatively and quantitatively determined by conventional techniques known to those skilled in the art: the amount of calcium is measured by XRF, the crystal structure of the compound is analyzed by XRD, the proportion of calcium carbonate and / or calcium oxide, if present, and calcium hydroxide is determined by thermogravimetry on a sample dried to constant weight at 150°C.
[0081] The additives present in the adsorbent can be qualitatively and quantitatively determined by NMR. The additives in the adsorbent can be determined by preparing samples that are dried to constant weight at 150° C. and mixed in a deuterated solvent or mixture of deuterated solvents, preferably a mixture of DO and CDCN, and then analyzed in a semi-liquid state by probe HR-MAS (high resolution magic angle spinning). 1 H NMR or 13 C NMR or a combination of both, and in the solid state 1 H NMR or in the solid state 13 It is also possible to measure by C NMR on solid samples dried to constant weight at 150 °C. Quantitative measurements by NMR can be made by comparing with a calibration curve obtained by preparing samples of the adsorbent containing various concentrations of the additive. In addition, lime-based adsorbents may contain moisture from the atmosphere or from the manufacturing process, so samples must be dried to constant weight before analysis.
[0082] The first additive is selected from the following: - the group of hydrogel-forming materials of synthetic origin, including polyacrylates, polyacrylic acid, crosslinked products of polyacrylates and polyacrylic acid, or crosslinked products of acrylamide and acrylic acid copolymers, especially those partially neutralized with sodium and / or potassium; or - a group of naturally occurring hydrogel-forming materials, including guar gum, alginate, dextran or xanthan gum, or combinations thereof; and / or - The group of cellulose ethers, including hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethylcellulose or hydroxyethylmethylcellulose (HEMC).
[0083] The superabsorbent polymer is selected from crosslinked polymers of acrylic acid or methacrylic acid, crosslinked graft copolymers of polysaccharide / acrylic acid or methacrylic acid, crosslinked terpolymers of acrylic acid or methacrylic acid / acrylamide / sulfonated acrylamide, and alkaline earth or alkali metal salts thereof.
[0084] In one embodiment the lime-based sorbent according to the invention further comprises sodium, wherein the amount of sodium expressed as its equivalent NaO oxide form in said lime-based sorbent measured by XRF is at least 0.1% by weight, preferably at least 0.3% by weight, preferably at least 0.5% by weight, preferably at least 0.7% by weight, preferably at most 15% by weight, preferably at most 7% by weight, preferably at most 5% by weight, preferably at most 2.5% by weight relative to the total weight of said sorbent in dry form.
[0085] Preferably, the lime-based adsorbent has a concentration of at least 3 m 2 / g, preferably at least 10m 2 / g, more preferably at least 20m 2 / g, preferably at least 40m 2 / g, the BET specific surface area being measured manometrically with nitrogen adsorption after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multipoint BET method described in the ISO 9277 / 2010E standard.
[0086] Preferably, the lime-based adsorbent has a pH of at least 0.01 cm 3 / g , preferably at least 0.05 cm 3 / g , more preferably at least 0.1 cm 3 / g , and more preferably at least 0.2 cm 3 / gwherein the total BJH pore volume is measured by manometry with nitrogen adsorption after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multi-point BJH method described in the ISO 9277 / 2010E standard.
[0087] In one embodiment, the lime based sorbent is a blend of the following: - Powder particles of slaked lime having a particle size distribution included in a first numerical range, and - powder particles of a first additive having a particle size distribution falling within a second range that overlaps or is equal to the first range.
[0088] The lime-based adsorbent according to the present invention can be obtained by a production method including the following steps. - Slaking quicklime with water in a hydrator via non-wet route; - recovering hydrated lime at the outlet of said hydrator; wherein the method further comprises adding at least a first additive; the first additive is selected from the group of hydrogel-forming materials of natural or synthetic origin, in particular from the group of superabsorbent polymers (SAPs) or from the group of cellulose ethers or from a combination thereof; The first additive is added before, during or after the slaking step and has a weight ratio to the weight of the slaked lime of 0.2-10 wt.%, preferably at most 5 wt.%, more preferably at most 2.5 wt.%, wherein the amount of slaked lime is expressed as equivalent CaO and the amount of the first additive is expressed as dry equivalent after drying at 150° C. to constant weight.
[0089] Preferably, the first additive is selected from the following: - the group of hydrogel-forming materials of synthetic origin, including polyacrylates, polyacrylic acid, crosslinked products of polyacrylates and polyacrylic acid, or crosslinked products of acrylamide and acrylic acid copolymers, especially those partially neutralized with sodium and / or potassium; or - a group of naturally occurring hydrogel-forming materials, including guar gum, alginate, dextran or xanthan gum, or combinations thereof; and / or - The group of cellulose ethers, including hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethylcellulose or hydroxyethylmethylcellulose (HEMC).
[0090] In one embodiment of the process, the first additive is added prior to or during the slaking step and is provided at least partially or wholly in a solution or suspension and is added to the water used for the slaking step.
[0091] In another embodiment of the production process, the first additive is added after the slaking step and is provided at least partially or wholly in a solution or suspension and is added to the hydrated lime, for example by sprinkling the additive on the recovered hydrated lime.
[0092] In another embodiment of the method, the first additive is added as a powder to the quicklime prior to the slaking step.
[0093] In another embodiment of the method, the first additive is added to the recovered slaked lime after the slaking step. Preferably, the first additive added after the slaking step is in the form of a powder.
[0094] In another embodiment of the method for producing a lime-based adsorbent according to the invention, the method further comprises the step of adding a second additive, which is an alkali metal salt or hydroxide, before and / or during and / or after the slaking step, in an amount sufficient to obtain the slaked lime, the alkali metal content, expressed in terms of alkali metal oxide, being 0.2% to 3.5% by weight based on the total weight of the slaked lime.
[0095] Preferably, the alkali metal salt or hydroxide is water soluble and may be selected from sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium phosphate, sodium persulfate or sodium acetate. Preferably, the alkali metal salt or hydroxide has a solubility in water at 20° C. of 50 or more. g / dm 3 Better than or equal to, preferably 100 g / dm 3 Better than or equal to, preferably 200 g / dm 3 Better than or equal to, preferably 300 g / dm 3 Better than or equal to, preferably 500 g / dm 3 Better solubility.
[0096] In one embodiment of the manufacturing method, the second additive is added before, during or after the slaking step, and the first additive is added after the slaking step, preferably in the form of a powder. The second additive may be added under the form of a powder or in the form of a solution.
[0097] In the method for producing a lime-based adsorbent according to the present invention, the residence time during which quicklime is slaked inside the hydrator is preferably comprised between 5 and 45 minutes, preferably between 20 and 40 minutes, and more preferably between 25 and 35 minutes.
[0098] In an embodiment of the method for producing a lime-based sorbent in which a first additive is added before or during the slaking step, the method further comprises the steps of drying the lime-based sorbent and / or cutting the lime-based sorbent into granules and / or grinding or milling the lime-based sorbent.
[0099] In another embodiment of the method for producing a lime-based sorbent, where the first additive is added to the slaked lime after the slaking step, the process further comprises: - cutting the recovered hydrated lime into granules so as to remove the fraction of particles outside a first value range; - cutting the powdered first additive into granules so as to remove a fraction of particles outside a second range of values overlapping or equal to the first range of values, in order to provide particles of hydrated lime and particles of additive having a similar particle size distribution; - mixing said hydrated lime and said first additive in a homogenizer.
[0100] In another embodiment of the manufacturing method according to the present invention, the process comprises the following steps. -d max and d min providing quicklime having a predetermined particle size distribution within a third particle size range defined by: - overlaps or is included within said third particle size range, and d max and d min providing the first additive having a particle size distribution falling within a fourth particle size range defined by: max and d min and said quicklime having a particle size distribution falling within a third particle size range defined by: - non-wet slaking the premix in a hydrator to obtain hydrated lime containing the first additive; - recovering hydrated lime at the outlet of said hydrator; - optionally drying the slaked lime; - optionally grinding the hydrated lime; - Optionally, sieving or air classifying the hydrated lime.
[0101] For example, the first additive is d min is 1μm or more, d max The powdered slaked lime can be classified so as to have a particle size distribution of 200 μm or less. min is 1μm or more, d max is 200μm or less, alternatively d min is 1μm or more, dmax is less than 20 μm, alternatively d min is 5μm or more, d max is less than 20 μm, alternatively d min is 20μm or more, d max is less than 35 μm, alternatively d min is 20μm or more, d max is less than 50 μm, alternatively d min is 50μm or more, d max is less than 100 μm, alternatively d min is 50μm or more, d max is less than 150 μm, alternatively d min is 100μm, d max The powder can be classified to have a particle size distribution of less than 200 μm.
[0102] In one embodiment of the method according to the invention, the first additive is added to the quicklime before the slaking step to form a premix which is fed to the hydrator for the slaking step. Providing a premix comprising quicklime and at least the first additive can be advantageous in terms of logistics and costs for plants with flue gas treatment equipment and hydrators.
[0103] The premix according to the present invention is composed as follows. - at least 70% by weight, more preferably at least 85% by weight, of quicklime, relative to the total weight of said premix in dry form after drying to constant weight at 150°C, and - at least 0.2% and up to 10% by weight, preferably at least 1% and up to 5% by weight, more preferably at least 1.2% and up to 2.5% by weight of a first additive, relative to the total weight of said premix in dry form after drying to constant weight at 150°C, wherein said first additive is selected from among hydrogel-forming materials of natural or synthetic origin, in particular from the group of superabsorbent polymers (SAP) or the group of cellulose ethers or a combination thereof.
[0104] Preferably, in the premix, the powdered quicklime and the powdered first additive are in the form of a powder blend comprising: -d max and d min and a powder particle of quicklime having a particle size distribution included in a third range of values of - overlapping or equal to the third range, d max and d min and a fourth range of values of the powder particles of the first additive.
[0105] In one embodiment of the premix, the quicklime is preferably subjected to a grinding step, optionally after a granulometric cutting step, by subjecting the quicklime to a grinding step. min and d max and the first additive is provided to have a particle size distribution defined by a first set of values of d min and d max Advantageously, the d of one of the quicklime or the first additive is selected to have a particle size distribution defined by a second set of values. 50 The value of is the other value d min and d max Preferably, the mixture is made of quicklime and the first additive. 50 Each value of d min and d max A similar particle size distribution of the quicklime and the first additive advantageously prevents segregation of both compounds.
[0106] In another embodiment, the premix may also include the second additive.
[0107] The lime-based sorbent according to the invention obtained from the process described herein is advantageously used in flue gas treatment processes including circulating dry scrubber processes or dry sorbent injection processes.
[0108] The present invention is also characterized in that an exhaust gas treatment process in which pollutant-containing gas is circulated through a duct before reaching a particulate control device includes a step of injecting a lime-based adsorbent as disclosed herein.
[0109] In one embodiment, the flue gas treatment process is a circulating dry scrubber process. Circulating dry scrubber (CDS) units or installations are well known in the art and are operated to remove pollutants from flue gases. CDS technology was initially developed for SO2 removal in coal-fired power plants. Today, it is also used to treat flue gases from industrial furnaces and boilers fueled by biomass, industrial waste, and municipal waste. The CDS process can remove both acid gas components and trace pollutants. The process is based on the recirculation of the filter residue, which consists of the reaction products of the sorbent and fly ash from the filter. The CDS unit uses a calcium-based sorbent.
[0110] A non-limiting example of a CDS is depicted in FIG. 1. The CDS installation 100 is located downstream of a gas burner 200, which is connected by a first duct 101 to the bottom of a reactor 102. A reservoir 107 containing fresh adsorbent is connected to the bottom of the reactor 102 by a second duct 108, and a metering device 109 is arranged between the second duct and the bottom of the reactor for injecting fresh adsorbent when needed. A gas 300 containing pollutants flows from the burner 200 through the first duct 101 and then through the reactor 102 where the pollutants react with the fresh adsorbent, and then the adsorbent partially reacted with the gas is filtered through a particulate filter device 103, which is located downstream of the reactor 102 and upstream of a stack 110. The particulate filter device 103 is composed of a number of baghouse filters 104. The reacted sorbent, unreacted sorbent, and optionally the fly ash collected in the baghouse filter 104 form a residue. The collected residue is removed from the baghouse filter 104 and falls into a hopper 105 at the bottom of the particulate filter device 103 while the pollutant-depleted exhaust gas is exhausted through a stack 110. The residue is directed to a conditioning mixer 106 consisting of a mixer shaft 111 where water is added to reactivate the residue before it is recycled to the reactor 102.
[0111] In the process of flue gas treatment using a circulating dry scrubber unit or installation according to the present invention, a fresh lime-based sorbent as disclosed herein is introduced into the CDS installation. The sorbent according to the present invention can provide a residue in the CDS process with good flowability, thereby preventing adhesion in the piping, ducts or other parts of the circulating dry scrubber unit or installation. The sorbent according to the present invention can release its water at low temperatures, typically at temperatures of the circulating dry scrubber unit or installation between 50°C and 350°C. The lime-based sorbent according to the present invention provides a residue in the CDS process that exhibits good flowability properties even at high humidity, also called water bearing, such as 10% by weight or more in the residue circulating in the circulating dry scrubber unit, with respect to the total weight of said sorbent in dry form.
[0112] In one embodiment, the flue gas treatment process is a dry sorbent injection (DSI) process. Such a process is simpler than a circulating dry scrubber process and involves dry injection of a lime-based sorbent as described herein into the flue gas before a filtering unit, typically a bag filter or an electrostatic precipitator. The lime-based sorbent reacts with the pollutants in a single pass.
[0113] The reaction between the gas phase pollutants and the adsorbent takes place in the reactor or exhaust gas duct and continues in a filter, typically a bag filter. The reaction products and fly ash from the process are captured in downstream filter devices.
[0114] One advantage of using the lime-based sorbent according to the invention in a dry sorbent injection process is that the first additive can capture moisture and thereby minimize adhesion to the sorbent storage silo or injection pipes connected to the flow gas duct. EXAMPLES
[0115] (Pilot plant description) The experiments were carried out in a CDS pilot unit which consists of three main connected units: the reactor, the filter means and the mixing zone. The reactor is a Venturi reactor, consisting of a vertical adiabatic tube (7 m long and 4 cm diameter).
[0116] At the bottom of the reactor there is an inlet for injecting a synthesis gas stream containing acid gases (N2, O2, H2O, CO2, SO2). The synthesis gas flows through the reactor and then passes through a baghouse filter placed at the top of the reactor. The baghouse filter consists of six sleeves, each of which is 0.1 m 2 It has an area of.
[0117] The temperature of the synthesis gas flow was measured at the baghouse filter and controlled by a heating resistor at the bottom of the reactor to be 100° C. at the baghouse filter.
[0118] The bottom of the reactor has an inlet for fresh adsorbent and an inlet for recycled material reacted with fresh adsorbent that has been circulated at least once in the reactor. Fresh adsorbent is introduced into the bottom of the reactor by pneumatic transport, while recycled material is introduced into the bottom of the reactor via a dosing screw. The ranges of injection rates are 0-300 g / h for fresh adsorbent and 0-6000 g / h for recycled material, respectively.
[0119] Solid particles of fresh sorbent and / or recycled material are entrained in a bag filter by the gas flow through the reactor. The bag filter (filter means) separates the gas from the solid particles consisting of at least partially reacted fresh sorbent and recycled material (residue).
[0120] The solid residue is then stored and conveyed by three hoppers equipped with butterfly valves: a buffer hopper, an extraction hopper from which a certain amount of product is removed to mass balance the system while fresh sorbent is injected, and a weighing hopper. The residue is then fed by a conveying screw into the conditioning mixer (mixing zone).
[0121] In the conditioning mixer, a predetermined amount of water is thoroughly mixed with the recycled material. The amount of water added to the recycled material can vary from 0.1% to a maximum of 30% by weight, based on the total weight of the adsorbent fed into the mixer. Water is injected into the mixer using a stainless steel hollow cone nozzle.
[0122] The conditioning mixer includes an elongated receiver having two shafts extending from a first end to a second end. The receiver of the conditioning mixer has a volume of about 7 dm 3The receiver has a capacity of 1000 mm. A first inlet for introducing the retentate in the receiver is located adjacent to the first end of the receiver, and a water injection nozzle for introducing water into the receiver to humidify the retentate is located downstream and adjacent to the first inlet. An outlet for discharging the humidified retentate out of the receiver is located at the bottom near the second end of the receiver. Two shafts are arranged in the receiver parallel to each other and equipped with directional flat plate paddles with interpenetrating rotation (central flow upwards). The shafts are fitted into a cylinder of a first diameter D1 and the outermost edges of the paddles are fitted into a cylinder of a second diameter D2. The central axes of both shafts are spaced from each other at a distance strictly longer than the first diameter D1 and less than the second diameter D2. The bottom surface of the receiver is profiled as a double round bottom that matches the rotating cylinder formed by the paddles, so that the paddles do not contact the double round bottom of the receiver. Each paddle of one shaft is offset from the paddle of the other shaft to allow the shaft to rotate. Each paddle of the same shaft is radially offset at an angle of 120° to the adjacent paddle. Near the first end of the receiver, both shafts have two first paddles oriented at 20° to the longitudinal axis of the shaft to convey the residue under the water injection nozzles. Both shafts further include five paddles downstream of the two first paddles oriented at an angle of 50° to the longitudinal axis of the shaft to create intensive backmixing and thus accumulation of residue in the mixing zone. Both shafts further include four final paddles arranged downstream of the said five paddles and oriented at an angle of 20° to the longitudinal axis of the shaft to gradually push the moistened residue out of the mixer. Such types of conditioning mixers are commonly used in CDS installations.
[0123] After the mixer, the moistened residue falls into a vertical hopper equipped with a bridge breaker and a conveying screw, which introduces the moistened residue back into the reactor.
[0124] The behaviour of the adsorbents according to the invention and of the comparative adsorbents was tested in a CDS pilot unit.
[0125] Increasing amounts of water were added to the converted solid material (less than 10% free lime) circulating through the conditioning mixer, resulting in a test protocol to evaluate the reaction in terms of product stickiness and overall CDS process operability.
[0126] In the first stage of the test protocol, unreacted and considered fresh sorbent was first placed in the presence of SO2 and CO2 to obtain the sorbent converted to residue. The conversion of the sorbent to residue was considered to be achieved when the available lime Ca(OH)2 in the residue was less than 10 wt%. To accelerate the conversion of the sorbent, unreacted fresh sorbent was added at once at the start of the test and no more fresh sorbent was added at later stages.
[0127] In the second stage of the test protocol, the amount of water added to the conditioning mixer is gradually increased while the residue is recycled to the CDS pilot unit until problems with the CDS pilot unit occur, such as pressure drop, clogging, and pasty residue. The highest water amount (% w / w) that allows nominal operation is the test result. A flowable residue with a relatively high moisture value is desired for the CDS pilot unit. The adsorbent providing such a residue to the CDS pilot unit is therefore more efficient in terms of SO2 capture and can be regenerated more times and recycled for longer periods, resulting in reduced adsorbent consumption.
[0128] [Comparative Example] In the comparative example, the fresh sorbent used is a sample of hydrated lime that does not constitute any additives. This hydrated lime is industrially produced in one of the applicant's hydration plants. In this plant, a three-stage hydrator (manufactured by the company Pfeiffer) is fed with 4 t / h of quicklime with a size of 0-3 mm and with water. The amount of water is adjusted so that the moisture content of the product leaving the hydrator is less than 1%. This moisture content is measured by loss on drying at 150°C. The temperature inside the hydrator is also used as a process control parameter, the temperature measured in particular in the second stage being typically in the range 100-105°C. From the outlet of the hydrator, the product is conveyed via a conveying screw and a bucket elevator to an air classifier. In this classifier, the product is separated into a coarse fraction (usually above 65 μm) and a fine fraction (usually below 65 μm), the latter being sent directly to a storage silo. The hydrated lime of the comparative example exhibits the following physical characteristics: - The moisture content is 1% by weight, measured by loss on drying at 150 °C. - BET specific surface area is 14 m 2 / g Here, this BET specific surface area is measured by manometry with nitrogen adsorption after degassing in a vacuum at 190°C for at least 2 hours, and calculated according to the multipoint BET method described in the ISO 9277 / 2010E standard. - Pore volume is 0.063 cm 3 / g where the pore volume is determined manometrically with nitrogen adsorption after degassing in vacuum at 190°C for at least 2 hours and calculated according to the BJH method described in the ISO 9277 / 2010E standard. - d98 less than 70μm as measured by laser granulometry in methanol after 2 minutes of sonication at 100W.
[0129] The comparative example hydrated lime is tested in the CDS pilot unit according to the test protocol described above. In the first stage of the test protocol, a quantity of 4.2 kg of fresh sorbent is loaded into the CDS pilot unit. The fresh sorbent is directly injected into the bottom of the reactor by the re-injection screw. The flow rate of the synthesis gas is 25 Nm 3 / h The composition of the gas mixture is shown in Table 1.
[0130] [Table 1]
[0131] The residue is separated from the gas by a baghouse filter and is automatically washed with an air pulse when the differential pressure on the filter reaches 6 mbar. The residue passes through a cascade of hoppers to a regulated mixer, where it is added at a flow rate of 2500 g / h and mixed with 250 mL / h of water to obtain a moisture content of 10%. This moistened residue is then recharged at the bottom of the reactor and recycled again. When the residue behaves well in terms of flowability, for example when 200 g of residue can be charged into the reactor in less than 120 seconds, typically after 7 hours, the recycle flow is increased to 4000 g / h and mixed with 400 mL / h of water to maintain a moisture content of 10%.
[0132] Twice a day, at intervals of at least 3 hours, a first sample of the residue is taken after the mixing zone and a second sample of the residue is taken in a weighing hopper (also corresponding to the reactor outlet) to analyze the content in carbonates, sulfur species (sulfates or sulfites) and unreacted Ca(OH)2 (available lime). The conversion of the sorbent to the residue can be considered to have been achieved if the available lime Ca(OH)2 in the residue is less than 10% by weight.
[0133] In the second step of the protocol, the gas flow rate was set to 25 m 3 / hThe temperature is maintained at 40°C and SO2 and CO2 injection is stopped. The residue recirculation flow rate is maintained at 4 kg / h and the humidity in the mixer is increased by 2% from 12% over a period of at least 3 hours until clogging or pressure drop problems occur.
[0134] After each humidity increase step, at least one sample is withdrawn from the mixer via a filter to determine the moisture content of each residue by weight loss drying at 150°C.
[0135] In the comparative sample, the maximum amount of water added to the mixer that the equipment could adequately handle was 18%. Beyond this limit, there was concern of a number of process problems (severe clogging, high pressure drop) caused by the high viscosity of the residue.
[0136] [Example 1] In this example, the slaked lime of the comparative example was used as a raw material, and Apromud from Aprotek was used. TM Particle size distribution d sold under the name P150XL max The superabsorbent polymer was mixed with a superabsorbent polymer, which is a reticulated sodium polyacrylate with a diameter of 400 μm or less (see, for example, FR 3 029 195). The superabsorbent polymer was used as received and already contained 5% moisture (measured by loss on drying at 150 °C), which may come from air trapped during handling and storage (storage at 0-35 °C). To produce 5 kg of the blend, 487.5 g of the above mentioned hydrated lime and 12.5 g of Apromud were added. TM Ten batches containing P150XL are mixed individually in a Turbula® shaker mixer for 10 minutes. The ten batches are then placed in a 20 L Planetary Mixer (Hobart) and mixed to produce a single batch of 5 kg. This batch contains Apromud TM The sample contained 2.5% by weight of P150XL. Another sample was prepared in the same way and was diluted with Apromud. TM A batch containing 10% P150XL is obtained.
[0137] Apromud TMThe blend containing 2.5% P150XL was analyzed prior to testing in the CDS pilot unit and its main properties were as follows: The moisture content, measured by loss on drying at 150°C, is 1.1% by weight. - BET specific surface area is 14.2 m 2 / g Here, this BET specific surface area is measured by manometry with nitrogen adsorption after degassing in a vacuum at 190°C for at least 2 hours, and calculated according to the multipoint BET method described in the ISO 9277 / 2010E standard. - Pore volume is 0.065 cm 3 / g where the pore volume is determined manometrically with nitrogen adsorption after degassing in vacuum at 190°C for at least 2 hours and calculated according to the BJH method described in the ISO 9277 / 2010E standard. - d98 less than 80μm as measured by laser granulometry in methanol after 2 minutes of sonication at 100W.
[0138] Apromud TM Blends containing 2.5% and 10% P150XL also 1 Characterization is carried out by 1 H NMR.
[0139] The additive was partially dissolved in a mixture of water and acetonitrile to prepare a trouble solution. TM 15 mg of P150XL is placed in a vial, mixed with 15 μl of D2O and 35 μl of CD3CN, and vigorously stirred for a few seconds to obtain a sample solution. The troublesome solution is analyzed by a probe dedicated to semi-solid mixtures, HR-MAS (high resolution magic angle spinning). 1 Analyze by 1 H NMR. 1 The H NMR spectrum was measured at room temperature with 64 scans, presaturated at 5000 Hz. TMP150XL gels in the presence of water, which is why most of the signals are larger. TM The spectrum of P150XL is shown in FIG.
[0140] Apromud TM 15 μg of the powder blend containing 10% P150XL was mixed with 20 μl of CD3CN and 40 μl of D2O in a vial to form a slurry. The slurry was analyzed by HR-MAS (high resolution magic angle spinning) with a probe dedicated to semi-solid mixtures. 1 Analyze by 1 H NMR. 1 The H NMR spectrum was measured at room temperature with 64 scans, presaturated at the water peak, and 5000 Hz rotation. TM The spectrum of the blend containing 10% P150XL is shown in FIG.
[0141] Apromud TM 15 μl of the powder blend containing 2.5% P150XL was mixed with 20 μl CD3CN and 40 μl D2O to form a slurry, which was analyzed by HR-MAS (high resolution magic angle spinning), a probe dedicated to semi-solid mixtures. 1 Analyze by 1 H NMR. 1 The H NMR spectrum was measured at room temperature with 64 scans, presaturated at 5000 Hz. TM The spectrum of the blend containing 2.5% P150XL is shown in FIG.
[0142] The spectra of both are similar, Apromud TM The blend containing 10% P150XL showed a stronger signal, and Apromud TM Auxiliary signals around 5 ppm were observed with P150XL alone and in the most concentrated sample. TM Comparing the spectra of P150XL alone and the blend, Apromud TMEven though there are some chemical shifts and even larger signals in the spectrum of P150XL alone, it was shown that there are similar signals, which are enclosed in Figure 2. These shifts and additional signals were determined by Apromud TM This can be explained by the difference in the behavior of the P150XL in water, Apromud TM P150XL gels completely upon absorption of water, whereas in the presence of lime a milky solution is obtained. Therefore, the probe HR-MAS was used 1 H NMR revealed that Apromud was produced in samples of the adsorbent according to the invention at relatively low concentrations of 2.5% based on the weight of the adsorbent. TM It is possible to detect the P150XL additive.
[0143] The above obtained hydrated lime-reticulated sodium polyacrylate blend is tested in the CDS pilot unit according to the test protocol mentioned above. In the first stage of the test protocol, a quantity of 4.2 kg of fresh sorbent (i.e., hydrated lime-reticulated sodium polyacrylate blend) is loaded into the CDS pilot unit. The fresh sorbent is directly injected into the bottom of the reactor by the re-injection screw. The synthesis gas flow rate set in this process is 25 Nm 3 / h and the composition is the same as that shown in Table 1 for the comparative example.
[0144] The residue is separated in a baghouse filter and automatically washed with an air pulse when the differential pressure on the filter reaches 6 mbar. Here the residue is introduced at a flow rate of 2500 g / h and mixed with 250 mL / h of water to obtain a wetness of 10%. This wetted residue is then recharged at the bottom of the reactor and recycled again. If the residue behaves well in terms of flowability, for example 200 g of residue can be dosed in the reactor in less than 120 seconds, typically after 7 hours the recirculation flow is set to 4000 g / h and mixed with 400 mL / h of water to maintain a wetness of 10%.
[0145] Twice a day, at intervals of at least 3 hours, a first sample of the residue is taken after the mixing zone and a second sample of the residue is taken in a weighing hopper (also corresponding to the reactor outlet) to analyze the content in carbonates, sulfur species (sulfates or sulfites) and unreacted Ca(OH)2 (available lime). The conversion of the sorbent to the residue can be considered to have been achieved if the available lime Ca(OH)2 in the residue is less than 10% by weight.
[0146] In the second step of the protocol, the gas flow rate was set to 25 m 3 / h The humidity is maintained at 12% and SO2 and CO2 injection is stopped. The residue recirculation flow rate is maintained at 4 kg / h and the humidity in the mixer is increased in 2% increments from 12% over a period of at least 3 hours until clogging or pressure drop problems occur.
[0147] After each humidity increase step, at least one sample is withdrawn from the mixer on a filter to determine the moisture content of each residue by weight loss drying at 150°C.
[0148] In the example samples, the maximum amount of water added to the mixer that the equipment could adequately handle was 28%: beyond this limit the residue becomes too pasty and the process becomes unfeasible.
[0149] Therefore, the slaked lime-reticulated sodium polyacrylate blend according to the present invention is capable of operating longer in a CDS pilot unit at higher moisture content compared to slaked lime with similar physical properties but without additives.
Claims
1. A powdered lime-based sorbent suitable for use in an exhaust gas treatment process for a circulating dry scrubber process, comprising: - at least 70% by weight of Ca(OH) relative to the total weight of said lime-based adsorbent in dry form after drying to constant weight at 150 ° C. 2 At least 3 m 2 / g BET specific surface area and a total BJH pore volume of at least 0.01 cm 3 / g; wherein the BET specific surface area is measured by manometry with adsorption of nitrogen after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multipoint BET method described in the ISO 9277 / 2010E standard; The total BJH pore volume was measured by manometry with nitrogen adsorption after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multi-point BJH method described in the ISO 9277 / 2010E standard. Ca(OH) 2 , and A lime-based adsorbent comprising at least 0.2% by weight and up to 10% by weight of a first additive, based on the total weight of said lime-based adsorbent in dry form after drying at 150° C. to constant weight, said first additive being selected from the group of hydrogel-forming materials of natural or synthetic origin, cellulose ethers and combinations thereof.
2. The lime-based adsorbent according to claim 1, The first additive is selected from superabsorbent polymers (SAPs), lime-based adsorbents.
3. The lime-based adsorbent according to claim 1, The first additive is selected from the following: the group of hydrogel-forming materials of synthetic origin, including polyacrylates, polyacrylic acids, crosslinked products of polyacrylates and polyacrylic acids, or crosslinked products of acrylamide and acrylic acid copolymers; or - the group of naturally occurring hydrogel-forming materials, including guar gum, alginate, dextran or xanthan gum or combinations thereof; and / or the group of cellulose ethers, including hydroxyalkyl or carboxyalkyl cellulose ethers; Lime-based adsorbent.
4. The lime-based adsorbent according to claim 2, A lime-based adsorbent, wherein the superabsorbent polymer is selected from the group consisting of crosslinked polymers of acrylic acid or methacrylic acid, crosslinked graft copolymers of polysaccharide / acrylic acid or methacrylic acid, crosslinked terpolymers of acrylic acid or methacrylic acid / acrylamide / sulfonated acrylamide, and alkaline earth or alkali metal salts thereof.
5. The lime-based adsorbent according to any one of claims 1 to 4, It further contains sodium, The equivalent Na in the lime-based adsorbent measured by XRF 2 A lime-based sorbent, the amount of sodium expressed as O-oxide form being at least 0.1% by weight of sodium relative to the total weight of said lime-based sorbent in dry form.
6. The lime-based adsorbent according to any one of claims 1 to 5, At least 10 meters 2 / g BET specific surface area, A lime-based adsorbent, wherein the BET specific surface area is measured by manometry with adsorption of nitrogen after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multipoint BET method described in the ISO 9277 / 2010E standard.
7. The lime-based adsorbent according to any one of claims 1 to 6, having a total BJH pore volume of at least 0.05 cm3 / g; wherein the total BJH pore volume is measured by manometry with nitrogen adsorption after degassing in vacuum at 190° C. for at least 2 hours and calculated according to the multi-point BJH method described in the ISO 9277 / 2010E standard for lime-based adsorbents.
8. A premix for use in a process for producing a lime-based adsorbent according to any one of claims 1 to 7, comprising: at least 70% by weight of quicklime, relative to the total weight of said premix in dry form after drying to constant weight at 150°C; and - at least 0.2% by weight and up to 10% by weight of a first additive, relative to the total weight of said premix in dry form after drying to constant weight at 150 ° C, The premix, wherein the first additive is selected from the group of hydrogel-forming materials of natural or synthetic origin, cellulose ethers, and combinations thereof.
9. A method for producing the lime-based sorbent according to any one of claims 1 to 7, suitable for use in an exhaust gas treatment process for a circulating dry scrubber process, comprising the steps of: - Slaking quicklime with water in a hydrator via the non-wet route; - recovering hydrated lime at the outlet of said hydrator; wherein the method further comprises adding at least a first additive; The first additive is selected from the group of hydrogel-forming materials of natural or synthetic origin, cellulose ethers, and combinations thereof; The method of manufacturing, wherein said first additive is added before, during or after the slaking step, and its weight ratio to the weight of said slaked lime is 0.2-10 wt. %, wherein the amount of said slaked lime is expressed in equivalent CaO and the amount of said first additive is expressed in dry equivalent after drying at 150° C. to constant weight.
10. 10. The method of claim 9, wherein the first additive is selected from the following: the group of hydrogel-forming materials of synthetic origin, including polyacrylates, polyacrylic acids, crosslinked products of polyacrylates and polyacrylic acids, or crosslinked products of acrylamide and acrylic acid copolymers; or - the group of naturally occurring hydrogel-forming materials, including guar gum, alginate, dextran or xanthan gum or combinations thereof; and / or the group of cellulose ethers, including hydroxyalkyl or carboxyalkyl cellulose ethers; Manufacturing method.
11. The method according to claim 9 or 10, said first additive is provided at least partially in solution or suspension and is added to said water and / or to said slaked lime; and / or the first additive is provided at least partially in solid form and is added to the quicklime and / or the slaked lime; Manufacturing method.
12. The method according to any one of claims 9 to 11, adding a second additive, which is an alkali metal salt or hydroxide, before and / or during and / or after the slaking step; the amount of alkali metal salt or hydroxide is sufficient to obtain said slaked lime, The content of the alkali metal, expressed in terms of the oxide of the alkali metal, is 0.2% by weight or more and 3.5% by weight or less based on the total weight of the slaked lime.
13. The method according to any one of claims 9 to 12, The method of the present invention comprises a residence time for slaking the quicklime inside the hydrator of between 5 and 45 minutes.
14. The method according to any one of claims 9 to 13, adding said first additive before or during said slaking step; drying the lime-based sorbent; and / or cutting the lime-based sorbent into granules; and / or The method further comprises the step of grinding or pulverizing the lime-based sorbent.
15. The method according to any one of claims 9 to 14, adding said first additive to said slaked lime after said slaking step; moreover, - cutting the recovered hydrated lime into granules so as to remove the fraction of particles outside a first value range; cutting said first additive in powder form into granules so as to remove a fraction of particles outside a second range of values overlapping or equal to the first range of values, in order to provide particles of hydrated lime and particles of additive having a similar particle size distribution; - mixing said slaked lime and said first additive in a homogenizer; Manufacturing method.
16. Use of the lime-based adsorbent according to any one of claims 1 to 7 or the adsorbent obtained by the process according to any one of claims 9 to 15, Use in exhaust gas treatment processes, including circulating dry scrubber processes.
17. An exhaust gas treatment process in which a gas containing pollutants is circulated through a duct before reaching a particulate control device, 8. A flue gas treatment process comprising the step of injecting a lime-based sorbent according to any one of claims 1 to 7.
Citation Information
Patent Citations
FR03029195A1
Slurried neutralizer for treatment of exhaust gas and treating method of exhaust gas
JP1997192449A
Calcium hydroxide composition
JP1997313932A
Process for manufacturing a sorbent for a flue gas treatment process, sorbent and use of said sorbent in such flue gas treatment process
WO2018185328A1
